Acrylamide exposure impairs blood-cerebrospinal fluid barrier function - Yao, Xue (Medknow Publications & Media Pvt Ltd, 2014)
Previous studies show that chronic acrylamide exposure leads to central and peripheral neu-ropathy. However, the underlying mechanisms remained unclear. In this study, we examined the permeability of the blood-cerebrospinal fluid barrier, and its ability to secrete transthyretin and transport leptin of rats exposed to acrylamide for 7, 14, 21 or 28 days. Transthyretin levels in cerebrospinal fluid began to decline on day 7 after acrylamide exposure. The sodium fluorescein level in cerebrospinal fluid was increased on day 14 after exposure. Evans blue concentration in cerebrospinal fluid was increased and the cerebrospinal fluid/serum leptin ratio was decreased on days 21 and 28 after exposure. In comparison, the cerebrospinal fluid/serum albumin ratio was increased on day 28 after exposure. Our findings show that acrylamide exposure damages the blood-cerebrospinal fluid barrier and impairs secretory and transport functions. These changes may underlie acrylamide-induced neurotoxicity.